Technology of Growing Dairy Production of Single-Breasted Camels in Different Pasture Types and Production of Shubat - A.A.K. Tleumuratov; B.S. Kalimbetov (Zien Journals, 2022)
This article presents the milk yield in the age dynamics of single-breasted camels and in different pasture types and shubat processing methods
Keywords: Dromedar; type; milk,; mes